2006
DOI: 10.1111/j.1600-0765.2005.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human growth/differentiation factor‐5 (rhGDF‐5) induced bone formation in murine calvariae

Abstract: Exposure to GDF-5 promotes proliferation and differentiation of calvarial cells, which give rise to ectopic bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…Because angiogenesis plays an important role in establishing blood flow to the fracture site in the bone repair process [Glowacki, 1998;Ferguson et al, 1999], Ad-GDF5-transduced hMSCs may be superior to cells combined with BMP2. However, other researchers have reported that BMP2 can promote heterotopic bone formation more strongly than GDF5 [Spiro et al, 2000;Yoshimoto et al, 2006]. This phenomenon may be explained by the different affinities of GDF5 and BMP2 for the BMP receptor IA (BMPR-IA) and BMP receptor IB (BMPR-IB).…”
Section: Discussionmentioning
confidence: 67%
“…Because angiogenesis plays an important role in establishing blood flow to the fracture site in the bone repair process [Glowacki, 1998;Ferguson et al, 1999], Ad-GDF5-transduced hMSCs may be superior to cells combined with BMP2. However, other researchers have reported that BMP2 can promote heterotopic bone formation more strongly than GDF5 [Spiro et al, 2000;Yoshimoto et al, 2006]. This phenomenon may be explained by the different affinities of GDF5 and BMP2 for the BMP receptor IA (BMPR-IA) and BMP receptor IB (BMPR-IB).…”
Section: Discussionmentioning
confidence: 67%
“…In vitro and in vivo studies suggested that the administration of GDF-5 with suitable carriers induced the formation of tendon-/ligament-like and cartilage/bone-like tissues in some rodents, ruminants and primates [4][5][6]. For bone tissue engineering GDF-5 has been used in combination with scaffolds such as collagen [5,7,8] or mineralized collagen [9] which, however, do not provide any biomechanical stability. Therefore, in a weight bearing situation additional stabilization is required [10].…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, comparative studies with the use of different growth factors are mandatory. Although the osteoinductivity of GDF-5 is well established, a reduced amount of ectopic bone is formed compared to other members of the TGF-b superfamily like BMP-2 [8,9]. We hypothesized that mutations of BMP-receptor-interacting residues of GDF-5 to amino acids present in BMP-2 may improve the bone formation capacity of the mutant GDF-5 to allow its extended use in bone regeneration.…”
Section: Introductionmentioning
confidence: 97%
“…In embryonic chondrogenesis, GDF-5 increases chondroprogenitor migration and condensation in vitro [8,9,15,21] and in vivo [15,46]. Exogenous GDF-5 induces de novo chondrogenesis [43], osteogenesis [11,26,29,39,40,50], tenogenesis [47], and angiogenesis [48]. Supplementation of GDF-5 to mesenchymal progenitor cells in culture increases chondrogenic pellet size [2], cellular proliferation [18,19], and stimulates the expression of chondrogenic and osteogenic markers [2,18,19,28,38,49,51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of GDF-5 induces de novo bone formation at ectopic sites [11,39,40] in applications such as spinal fusion [26,39,40], nonunion repair [39,40], and calvarial defects [29,50]. However, GDF-5 is less osteogenic than the more commonly used members of the TGF-b family, such as OP-1 [18,19].…”
Section: Introductionmentioning
confidence: 99%